(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Utama RS, Hadi TA, Hermanto B, Giyanto, Budiyanto A. 2022. Changes in reef benthic communities in Sumba Timur, East Nusa Tenggara, Indonesia.Biodiversitas 23: 677-687. Anthropogenic impacts and coral bleaching due to rising sea surface temperature have been severe and often, as of late on the worldwide scale, influencing the composition of coral reef benthic communities from coral to algal-ruled reefs (phase shift). In any case, coral reef phase shift does not continuously happen, considering corals can recoup when stressors occur. This considers points to examine the alteration in coral reef benthic communities and the relationship among benthic categories. The study was carried out in 2018 and 2021 at 10 stations within East Sumba, and East Nusa Tenggara. Underwater photo transect (UPT) was used to examine benthic cover at a depth of 6 to 9 m in reef slope. The result demonstrated that the benthic communities were slightly altered, especially hard coral, sponge, and other biotas. A slight recovery of hard coral cover is shown in 2021, followed by the decline of sponge and fleshy seaweed cover, which is shown in most observation sites. Acropora spp., Seriatopora spp., and Stylophora spp. were the three genera that increased in cover. The study also found the relationship between the benthic gradient and species richness and the number of colonies, which is gradient changes in benthic composition were in line with the change in hard coral species richness and colony numbers. Although hard coral increase significantly changes over time, it’s not altered the coral communities.